FoMO (Fear of Missing Out) on Impulsive Buying of Skintific Among Gen Z: A Conceptual Framework - Syafitri, Indah (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The development of technology and social media has significantly influenced consumer behavior, particularly among Generation Z, who are more connected to digital platforms than any other generation. One emerging phenomenon that has gained attention in this context is FoMO (Fear of Missing Out), a psychological response to the anxiety of missing out on experiences or information that others have, often aggravated by constant exposure to social media updates. This anxiety can drive individuals, particularly younger consumers, to engage in impulsive buying behaviors as a means to ease their fear of being left out. This research aims to investigate the impact of FoMO on impulsive buying, with a particular focus on the Skintific brand, a popular beauty product among Gen Z. The methodology employed in this study includes a literature review on FoMO and impulsive buying behavior, discussing key issues and concepts related to these variables as explored in previous research. While existing studies highlight a significant relationship between FoMO and impulsive buying, specific studies focusing on this dynamic within the context of beauty product purchases among Gen Z remain limited. The current lack of empirical data on this relationship emphasizes the need for further exploration, which this research seeks to address by constructing a conceptual framework that emphasizes both variables and their interconnections.